New Developments in Blastomycosis - Smith, Jeannina A.; Gauthier, Greg (Seminars in Respiratory and Critical Care Medicine, 2015)
Blastomyces dermatitidis, the etiologic agent of blastomycosis, is a thermally dimorphic fungus that grows as a filamentous mold in the environment and as budding yeast in human tissue. This pathogen is endemic to North America, particularly in the states bordering the Mississippi and Ohio rivers, the Great Lakes, and the St. Lawrence Seaway. Infection with B. dermatitidis causes a broad array of clinical manifestations ranging from asymptomatic infection to fulminant sepsis with acute respiratory distress syndrome and death. B. dermatitidis can infect almost any organ in the body, but has a predilection for lungs and skin. There have been recent advances in the understanding of the pathogenesis, diagnosis, and treatment of this fungus. The Infectious Diseases Society of America published updated guidelines in 2008 to guide clinicians in the treatment of this important pathogen.
Keywords: blastomycosis; Blastomyces dermatitidis; amphotericin; itraconazole